NMPC-Based 3D Path Tracking of a Bioinspired Foot-Wing Amphibious Robot - Heqiang Cao; Hailong Wang; Zhiqiang Hu (Journal of Marine Science and Engineering, 2025)
To achieve accurate 3D path tracking of a foot-wing hybrid-driven amphibious biomimetic robot under periodically varying forces, this study analyzes the periodic propulsion forces generated by the flapping motion of the robot’s feet and wings, along with the nonlinear hydrodynamic effects during underwater motion. To simplify the resulting complex force expressions, the scaling function averaging method is applied. Consequently, an accurate six-degree-of-freedom (6-DOF) dynamic model is established, in which the characteristic parameters of foot-wing flapping are adopted as control inputs. Based on this dynamic model, a nonlinear state-space representation of the robot’s underwater motion is constructed. In this formulation, 3D path tracking—derived from the Line-of-Sight (LOS) guidance method—and attitude stabilization are jointly defined as control objectives. To this end, a nonlinear model predictive control (NMPC) algorithm is employed to compute optimal control inputs, as it effectively addresses the challenges of strong nonlinearity, coupling effects, and multi-objective optimization. Finally, simulation experiments are conducted to validate the proposed control strategy. The results demonstrate that the robot is capable of accurately following the desired path. Furthermore, compared with conventional PID control, the NMPC approach significantly improves tracking stability and enhances the overall motion performance.